1997
DOI: 10.1029/96jd03322
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical modeling of hydroxyl and its relationship to other species during the Tropospheric OH Photochemistry Experiment

Abstract: Abstract. Because of the extremely short photochemical lifetime of tropospheric OH, comparisons between observations and model calculations should be an effective test of our understanding of the photochemical processes controlling the concentration of OH, the primary oxidant in the atmosphere. However, unambiguous estimates of calculated OH require sufficiently accurate and complete measurements of the key species and physical variables that determine OH concentrations. The Tropospheric OH Photochemistry Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
105
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 55 publications
15
105
0
Order By: Relevance
“…(1) Recent tropospheric field measurements have shown that there is still a significant disagreement between measured OH concentrations and the predictions from regional scale models [Crosley, 1997;McKeen et al, 1997]. Isoprene can be a major OH sink under certain conditions accounting for up to 30% of the OH removal rate [Biesenthal and Bottenheim, 1998 …”
Section: Oh + Csi-ia --• Productsmentioning
confidence: 99%
“…(1) Recent tropospheric field measurements have shown that there is still a significant disagreement between measured OH concentrations and the predictions from regional scale models [Crosley, 1997;McKeen et al, 1997]. Isoprene can be a major OH sink under certain conditions accounting for up to 30% of the OH removal rate [Biesenthal and Bottenheim, 1998 …”
Section: Oh + Csi-ia --• Productsmentioning
confidence: 99%
“…Hence it is an ideal target species to test the accuracy of tropospheric chemical mechanisms via comparison of measured [OH] with predictions of zero-dimensional models constrained by supporting measurements of the longerlived OH co-reactant trace gas concentrations, and photolysis rates, that define its rate of production and loss. Tropospheric measurements of OH concentrations have been made in various environments for about two decades , and references therein) together with supporting measurements, and, whilst the measured/modelled agreement has in general improved, there remain discrepancies Carslaw et al, 1999;McKeen et al, 1997;Bell et al, 2003). A commonly suggested hypothesis for model over-prediction of [OH] is an incomplete suite of supporting measurements of trace gas compounds that act as OH sinks .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these compounds have important implications for modeling the chemistry in the atmosphere. For example light carbonyls such as formaldehyde and acetone can influence the HOx budget in the upper troposphere (Mckeen et al, 1997). Acetone and acetaldehyde can also be converted to acetyl peroxy radicals by atmospheric oxidation and lead to formation of PAN (peroxyacetic nitric anhydride) type compounds, which act as relatively long-lived reservoirs for nitrogen oxides (NOx) (Roberts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%